Konde Cepol Betawi: Pengetahuan Tradisional, Identitas Budaya, dan Pewarisan Lintas Generasi - Elisabeth Soelandjani; Retno Wulandari; A. Sri Ariyanti; A.Titiek Wedowati (Indonesian Character Journal, 2026)
The Betawi konde cepol is an important element of traditional Betawi hairstyling that functions not only as a form of hair arrangement but also as a representation of aesthetic, symbolic, and socio-cultural values. Knowledge of the konde cepol has been transmitted from generation to generation through everyday practices, customary activities, and the role of women within family and community settings. However, changes in lifestyle, modernization, and the declining regeneration of cultural practitioners have posed challenges to the sustainability of this traditional knowledge. This study aims to examine the Betawi konde cepol as a form of intergenerational traditional knowledge, encompassing its history, production techniques, philosophical meanings, and the natural, layered, and adaptive patterns of knowledge transmission. This research employs a qualitative approach through literature review, observation, and interviews with Betawi cultural practitioners and activists. The findings indicate that the Betawi konde cepol plays a significant role in strengthening Betawi cultural identity by representing values of simplicity, neatness, and the elegance of Betawi women. Preservation efforts through tutorial activities involving youth participation, cultural education, festival organization, documentation initiatives, and proposals for recognition as intangible cultural heritage are strategic steps to ensure the sustainability and continued relevance of Betawi konde cepol traditional knowledge for younger generations.